Development of Assessment Instruments Mathematic Creative Thinking Ability on Junior High School Students - widiansah, Krisna nur; Kartono, Kartono; Rusilowati, Ani (Journal of Research and Educational Research Evaluation, 2019)
The development of creative thinking skills is one focus in learning mathematics. The ability to think creatively is needed in solving mathematical problems including the steps in the formulation, interpretation, and resolution of models or problem solving. This study aims to develop an instrument of assessment of creative thinking skills in mathematics in junior high school subjects. Research using the Borg & Gall development method. Data collection through the provision of test descriptions. The test instruments were validated by 7 experts who were analyzed using the Aiken'V formula and the field test of creative thinking ability was analyzed using the construct validity of Confirmatory Factor Analysis (CFA), reliability was analyzed using Alpha Cronbach. The results of the validation from the experts show validity ≥ 0.75 Aiken’s table that all items are valid, Test the validity of the items from the 4 item test items tested, all 4 item description items are valid with a coefficient> 0.3, and the value of the reliability coefficient > 0.6, construct validity value of KMO of 0.831 with a significance of 0,000 for 4 items that make up 4 factors according to the dimensions of aspects of creative thinking namely fluency, flexibility, authenticity and detail. The profile of mathematical creative thinking abilities in small and large scale trials is quite creative. The final product of the research is a valid, reliable and practical mathematical creative thinking appraisal instrument. The assessment of mathematical creative thinking can be used by the teacher to get information about how the creative thinking abilities possessed by each of the eighth grade students of Junior High School.